Regrouping stress in confined heifers - Almeida, Douglas Henrique Silva de (2023)
In commercial-scale confined herds, the exchange of animals in the flocks is common, regardless of color, breed, performance, sex, and category, which may be the criteria for the formation or even mixing of animals in the feeding pens. However, these exchanges interfere with the pre-established dominance hierarchy, creating situations of fights that determine the new social structure, leading to a negative impact on animal performance. The objective of this study was to evaluate aspects of feeding behavior, performance, and reactivity during regrouping in new flocks throughout the confinement cycle. Two studies were conducted at the Fernando Costa Campus (FZEA) of the University of São Paulo, Brazil. In the first study, eighty-nine Angus × Nelore heifers (315±3.4 kg, were used. The treatments consisted of four regroupings every 28 days: Regrouping 1, the animals were randomly allocated to lots (day 1, control). In regroupings 2, 3, and 4, two heifers from each lot were allocated to different lots. Animals were weighed, and their behavior was observed for three consecutive days after the three regroupings during the feedlot cycle. Agonistic interactions (fighting, head-butting with and without displacement, trough, and/or trough dispute) were quantified per flock to generate Elo classifications to identify the hierarchical status. In the second study, regroupings were performed due to the standardization of flocks by weight to evaluate the effects on animal temperament, performance, and the occurrence of disputes during feedlot confinement. Eighty-three Angus × Nelore heifers at ten months of age were confined to four stalls. After the second weighing, the heifers were subjected to three regroupings during a 1-month period (days 28, 56, and 84 of confinement), following the weight parameters, with the heifers 25% heavier allocated to lot 1 (n = 20), the animals between 26-50% of weight allocated to lot 2 (n = 21), the next 25% placed in lot 3 (n = 21), and the bottom 25% allocated to lot 4 (n = 21) at each weighing. Reactivity during weighing and exit velocity were measured before and after the third regroup. Agonistic behavior was analyzed on three consecutive days after each regrouping and on point days after the sequential days. The results were used to classify the animals into social classes (dominant, intermediate, and subordinate) by batch and Elo classifications. However, the results of the first experiment demonstrated the effects of the days after lot change on the frequency of fighting (p < 0.01) and head-butting with displacement (p < 0.001). The final social position remained the same for 54% of contemporary animals, differing substantially from that of regrouped individuals. There were higher odds of eating animals prior to regrouping 2 as well as higher odds of rumination (p < 0.001). Regrouping effects were observed for body weight (p < 0.05). Regrouping is a source of stress in confined heifers, altering the initial social structure and increasing the occurrence of agonistic interactions and conflicts, resulting in low average daily gains. In the second experiment, results showed slope values ranging from 0.55 to 0.91 in the flock hierarchy. The heifers showed a flat, non-transitive hierarchy. Animal performance was measured in terms of the average daily weight gain during the experimental period. Correlations among reactivity, daily activities, social behavior, and animal performance were evaluated. The Elo score showed a negative correlation with interactions in both regroupings (rfirst = 0.70, P < 0.05, and rthird = 0.77, P < 0.05). In both regroupings, there was a significant positive correlation between evaluations of Elo and degree centrality (rfirst = 053, P < 0.05; rthird = 0.79, P < 0.05), indicating that dominant animals also play a central role in agonistic interaction networks. There was a significant increase in final reactivity (P = 0.01) and final exit velocity, both of which were influenced by regrouping (P = 0.01). The number of fights differed between regroupings (P = 0.01), with the highest number of occurrences observed after regrouping 1 (1.51 ± 0.14). Similarly, the number of fights differed between days (P < 0.01), decreasing each day post-regrouping. Mean daily weight gain was greater before regrouping (P < 0.01). In general, regrouping is a source of stress in confined heifers, altering the initial social structure, increasing the occurrence of agonistic interactions and conflicts, and resulting in low average daily gains. However, agonistic interactions decreased over time in both experiments.